2021
DOI: 10.1111/jcpe.13510
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation and the relationship between periodontitis, edentulism, and all‐cause mortality: A 17‐year prospective cohort study

Abstract: Aim The aim was to investigate the role of systemic inflammation in the relationship between periodontitis, edentulism, and all‐cause mortality in a group of men in Northern Ireland aged 58–72 years. Materials and methods A representative sample of 1558 men had a detailed dental examination between 2001 and 2003. The primary end point was death from any cause. Cox's proportional hazards model was used to assess the longitudinal relationship between periodontitis, edentulism, and all‐cause mortality. Accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…12,26 A recent study also found that systemic inflammation only accounts for 10% of the mediating pathway effect that links PD with an increased risk of all-cause mortality. 27 Other findings suggest that PD treatment may also improve the efficacy of antihypertensive medication; although this study was limited to cross-sectional data, and the impact to subsequent systemic disease outcomes was not explored. 28 More robust research is needed to improve understanding of the biological mechanism that underpins the causal association between PD, hypertension, and systemic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,26 A recent study also found that systemic inflammation only accounts for 10% of the mediating pathway effect that links PD with an increased risk of all-cause mortality. 27 Other findings suggest that PD treatment may also improve the efficacy of antihypertensive medication; although this study was limited to cross-sectional data, and the impact to subsequent systemic disease outcomes was not explored. 28 More robust research is needed to improve understanding of the biological mechanism that underpins the causal association between PD, hypertension, and systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The latter authors suggest that PD treatment may reduce inflammation in hypertensive participants, 13 although the research regarding CRP as an inflammatory mediator between PD and hypertension is controversial 12,26 . A recent study also found that systemic inflammation only accounts for 10% of the mediating pathway effect that links PD with an increased risk of all‐cause mortality 27 . Other findings suggest that PD treatment may also improve the efficacy of antihypertensive medication; although this study was limited to cross‐sectional data, and the impact to subsequent systemic disease outcomes was not explored 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The BSO uses death registration information supplied by the NI Register General Office and other sources to link data on all deaths in NI to the master patient index. The BSO provides six monthly updates on the deaths of participants in the cohort who are flagged on their system [ 39 ]. The end of follow-up date for mortality was November 30 th , 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the genetic information was obtained from blood samples taken at rescreen. If a blood sample was unavailable from rescreen, residual blood from baseline samples was used for genotyping in a small number of cases [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Poverty-income ratios (PIRs) were collected and categorized according to the ratio of family income to poverty thresholds. These other covariates were determined because they have been proposed as confounding factors between periodontitis and mortality (Winning et al, 2021;Wu et al, 2021).…”
Section: Other Covariatesmentioning
confidence: 99%